2015
DOI: 10.1007/s00280-015-2698-7
|View full text |Cite
|
Sign up to set email alerts
|

Germline TYMS genotype is highly predictive in patients with metastatic gastrointestinal malignancies receiving capecitabine-based chemotherapy

Abstract: Germline polymorphisms of DPYD, TYMS and GSTP1 have a significant effect on toxicity and clinical outcome in patients receiving capecitabine-based chemotherapy for advanced colorectal or gastroesophageal cancer. These data should further be validated in prospective clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 30 publications
1
50
0
3
Order By: Relevance
“…Due to the limited number of 35 patients available for genotyping and without correction for multiplicity, a random correlation cannot be excluded. In a recent study, apparently no significant effect of this MTHFR polymorphism on pharmacokinetics or effects of capecitabine was found when given as a component of an epirubicin/cisplatin/capecitabine regimen to 76 patients with advanced gastroesophageal cancer [29], while the number of samples available for pharmacokinetic analysis and many other details of this analysis have not been provided and thus exclude a detailed assessment of this result. The previous finding for 5-FU [28], however, together with the present result suggests that an indirect relationship or a yet unknown mechanism is possible; this should be investigated in further studies.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Due to the limited number of 35 patients available for genotyping and without correction for multiplicity, a random correlation cannot be excluded. In a recent study, apparently no significant effect of this MTHFR polymorphism on pharmacokinetics or effects of capecitabine was found when given as a component of an epirubicin/cisplatin/capecitabine regimen to 76 patients with advanced gastroesophageal cancer [29], while the number of samples available for pharmacokinetic analysis and many other details of this analysis have not been provided and thus exclude a detailed assessment of this result. The previous finding for 5-FU [28], however, together with the present result suggests that an indirect relationship or a yet unknown mechanism is possible; this should be investigated in further studies.…”
Section: Discussionmentioning
confidence: 86%
“…A polymorphism in MTHFR (677 C > T; A222V) reduces enzyme activity and presumably increases the level of 5,10-methylenetetrahydrofolate. This increase may be correlated with an improved response to 5-FU [9], although respective results are equivocal [29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a correlation between the DPYD*2A variant and reduced enzyme activity in peripheral blood mononuclear cells (PBMCs) was found in several ex vivo studies that confirmed decreased function of DPYD*2A [26,[28][29][30] and consequently an association was also found between DPYD*2A and reduction in fluoropyrimidine clearance in patients [31,32]. In numerous studies an association between DPYD*2A allele carriership and the increased risk of toxicity related to fluoropyrimidine treatment was confirmed [4,24,31,[33][34][35][36][37][38][39][40][41][42][43][44][45]. For example, in a meta-analysis by Terrazzino et al a strong correlation between the DPYD*2A allele and overall grade ≥3 toxicity was found (odds ratio 5.42, p < 0.001) [33].…”
Section: Previous Guidelines and Recommendationsmentioning
confidence: 88%
“…Simultaneously, our work was [4,8,10,11,19,27,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] DPYD*13 (rs55886062) [4,19,30,32,33,46,49,50] 0.5 c.2846A>T (rs67376798) [4,13,24,33,36,41,42,44,47] c.1236G>A/ HapB3 (rs56038477) [14,15,42,44,46,47,49,50,56] 1 DPYD*1 (wild-type)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation